2.76. Wyznacz pochodną funkcji: f(x) = 1/4 * x ^ 4 – 1/3 * x ^ 3 + 2x ^ 2 c) f(x) = – 3x ^ 8 + 5x ^ 4 + 6 e) f(x) = sqrt(6) * x + x ^ 7 – 1/8 * x ^ 8 x 0 =-2 x 0 =0 x 0 =1 x 0 =-3 x 0 =0 x 0 =2 b) f(x) = – 3x d) f(x) = – x ^ 2 + 7 ) f(x) = x ^ 3 – 4x ^ 2 + 5x b) f(x) = x ^ 5 – 2x ^ 4 + x + 1 f(x) = 5 + 2x ^ 3 – 6x ^ 6 f) f(x) = x ^ 10 + x ^ 100 + x ^ 1000

2.76. Wyznacz pochodną funkcji: f(x) = 1/4 * x ^ 4 – 1/3 * x ^ 3 + 2x ^ 2 c) f(x) = – 3x ^ 8 + 5x ^ 4 + 6 e) f(x) = sqrt(6) * x + x ^ 7 – 1/8 * x ^ 8 x 0 =-2 x 0 =0 x 0 =1 x 0 =-3 x 0 =0 x 0 =2 b) f(x) = – 3x d) f(x) = – x ^ 2 + 7 ) f(x) = x ^ 3 – 4x ^ 2 + 5x b) f(x) = x ^ 5 – 2x ^ 4 + x + 1 f(x) = 5 + 2x ^ 3 – 6x ^ 6 f) f(x) = x ^ 10 + x ^ 100 + x ^ 1000

Kliknij aby dołączyć do Akademii Matematyki

Dodaj komentarz